MODELO MATEMÁTICO DE SIMULACIÓN CONTINUA PARA COORDINAR INVENTARIOS APLICADO A UNA RED LOGÍSTICA - CESAR AUGUSTO PINEDA PEREZ; ERIKA YAMILE BERNAL; KAREN VIVIANA LOPEZ; ANDRÉS CAMILO LEON; DANIEL HOLGUIN (Revista Ingeniería, Matemáticas y Ciencias de la Información)
This article presents a mathematical model of continuous simulation to coordinate the inventories in a logistics networkmanufacturer-distributor-retailer-client considering the accumulated deficit and dispatch of the deficits of each one of theactors of the network attending to the delays that appear in the flow of information and the flow of physical goods andtheir effects on system variables (state variables, flow variables, auxiliary variables).